Immunobiological properties of inactivated anti-highly pathogenic avian influenza vaccines based on antigens of А/Н5N1 avian influenza virus strains of different virulence - S. V. Frolov; I. A. Chvala; N. V. Moroz; V. Yu. Kulakov; V. Yu. Sosipatorova; D. B. Andreychuk (Ветеринария сегодня)
Antigen of H5N1 low pathogenic avian influenza virus Yamal strain included in the inactivated emulsion vaccine is able to induce strong immunity against highly pathogenic avian influenza in chickens. Inactivated emulsion vaccines based on antigen of H5N1 low pathogenic avian influenza virus Yamal strain and antigen of H5N1 highly pathogenic avian influenza virus А/chicken/Primorsky/85/08 strain are capable of inducing dose-dependent cross immunity against current Н5N1 and H5N8 highly pathogenic avian influenza viruses. Thus, inoculation dose of H5N1 low pathogenic avian influenza virus Yamal strain antigen required for protection of 95% of chickens against H5N1 highly pathogenic avian influenza virus А/chicken/Primorsky/85/08 strain and against H5N8 highly pathogenic avian influenza virus A/duck/KChR/1590-20/20 in the vaccine inoculation volume shall be at least 609 HAU and 255 HAU, respectively. The inoculation dose of H5N1 highly pathogenic avian influenza virus А/chicken/Primorsky/85/08 strain antigen for protection from H5N8 highly pathogenic avian influenza virus A/duck/KChR/1590-20/20 strain shall be at least 294 HAU. Protective effect of the tested inactivated vaccines was associated with humoral immunity level in poultry. Predicted titre of antibodies to homologous virus antigens conferring expected 95% protection of vaccinated poultry was 1:538 or 9.1 log2. Inactivated vaccine based on H5N1 low pathogenic avian influenza virus Yamal strain antigen demonstrates its high immunogenicity in chickens infected with Н5N1 and Н5N8 highly pathogenic avian influenza influenza virus.